Perioperative hemostatic management of patients with type A aortic dissection - Erdoes, Gabor; Ahmed, Aamer; Kurz, Stephan D.; Gerber, Daniel; Bolliger, Daniel (Frontiers in Cardiovascular Medicine, 2023)
Coagulopathy is common in patients undergoing thoracic aortic repair for Stanford type A aortic dissection. Non-critical administration of blood products may adversely affect the outcome. It is therefore important to be familiar with the pathologic conditions that lead to coagulopathy in complex cardiac surgery. Adequate care of these patients includes the collection of the medical history regarding the use of antithrombotic and anticoagulant drugs, and a sophisticated diagnosis of the coagulopathy with viscoelastic testing and subsequently adapted coagulation therapy with labile and stable blood products. In addition to the above-mentioned measures, intraoperative blood conservation measures as well as good interdisciplinary coordination and communication contribute to a successful hemostatic management strategy.